DURSASANA GUGUR: SEBUAH KAJIAN RESEPSI - Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2016)
A valuable literary work will get continually perception from its surrounding society. Problem of thisresearch is how the perception of society towards the death of Dursasana is. The study aims todescribe the various perceptions towards Dursasana’s death. Based on the perception approach,finding of this research shows that the death of Dursasana gets perception on five thingsincluding the name of Dursasana, his reason to join in the war, the place of his death, the way heis killed, and the finding of the legend village around Kroya, Cilacap.Keywords: literature, perception, the death, Dursasana.